Theoretical analysis and application of the telluric electric field frequency selection method for shallow groundwater exploration - Wang, Danqi; Yang, Tianchun; Isah, AbdulGaniyu; Qin, Qin; Zhu, Maoyue (Frontiers in Earth Science, 2025)
The telluric electric field frequency selection method (TEFSM) measures horizontal electric field components at discrete frequencies of naturally occurring electromagnetic (EM) fields. Developed as an extension of magnetotellurics (MT) and audio-frequency magnetotellurics (AMT), TEFSM offers potential for shallow groundwater exploration, yet its underlying mechanisms and practical effectiveness remain underexplored. Here, we combine theoretical analysis, forward modeling, and field validation to assess its performance. A conductive sphere model subjected to magnetotelluric and stray current fields was used to compute secondary surface responses, revealing low-potential anomalies directly above the target. The anomaly amplitude decreases with increasing burial depth and decreasing sphere radius. Field validation under the Rural Drinking Water Safety Project in Guangxi Province, China, involved 131 TEFSM-guided wells drilled to depths of up to 142.8 m. Of these, 114 yielded >1 m3/h, corresponding to an ∼87% success rate. The close agreement between simulations and field outcomes demonstrates that TEFSM reliably detects shallow conductive structures and is an effective tool for groundwater exploration.